Efektivitas Penerapan Buku Metode Takallam untuk Meningkatkan Maharah Kalam Siswa Kelas VIII MTsN 3 Blitar - Muttaqiyyah, Almar’atul; Nidak, Khoiru; Muslimah, Maziyyatul (Al-Wasil, 2023)
This article discusses the effectiveness of the application of the "takallam method book" containing material for uslub, maqtho', conversation, contemporary vocabulary accompanied by Indonesian translations and exercises to improve students' maharah kalam in class VIII MTsN 3 Blitar. This study aims to overcome problems in learning kalam, especially school reference books which are felt to be lacking in material terms and students find it difficult to use them. This study uses a quantitative approach to the type of experiment, because there is a need for a trial of the "takallam method book" which has never been applied in the research place, so it requires statistical data to prove the research hypothesis. The data collection methods include interviews, documentation, pre-test and post-test. The results of the study show that: 1) The steps for implementing the takallam method book are in the form of preliminary, core, and closing activities. 2) The results of increasing student's maharah kalam which proved effective with SPSS calculations from the Independent Sample t Test showed a sig (2-tailed) value of 0,012 < 0,05, so Ho was rejected and Hi was accepted. 3) The advantages of the takallam method book include complete and easy-to-understand kalam material, lots of example sentences for the practice of kalam, complete Arabic sentences, contemporary mufrodat and equipped with Indonesian translations. While the weakness is that there are contemporary mufrodat that are still not common to students and few pictures in the material.